Development and validation of a physics achievement test to identify instructor variables associated with physics achievement of engineering students of Region V - Lita, Bernarda M. (Animo Repository, 1986)
This study aims to develop and validate a physics achievement test and using this to identify the instructor variables associated with achievement in physics of engineering students of Region V. The draft of the test subjected for try-out and validation consisted of 150 multiple choice items. After an item analysis, the final form consisted of sixty (60) multiple choice items. The reliability coefficient of the test was found to be 0.73 using the Kuder Richardson Formula 20.To collect data on the instructor variables and the achievement of the students, the descriptive method of research was employed utilizing a questionnaire, faculty morale scale, achievement test and mental ability test. The ANCOVA showed that the achievement in physics of students under instructors with high faculty morale is significantly higher than the students whose instructors have low morale. No significant differences in the student achievement under the other types of instructors were observed. Furthermore, no significant relationships were observed between the achievement in physics and the other instructor variables under consideration. Stepwise regression on the other hand, showed that the following instructor variables are good predictors of the students' achievement in physics, namely: (a) faculty rank, (b) status of appointment, and (c) faculty morale. The best among these predictors is the faculty rank of the physics instructors.